RAB27A is an independent prognostic factor in clear cell renal cell carcinoma. (21st January 2019) - An, Hyo Jung; Song, Dae Hyun; Koh, Hyun Min; Ko, Gyung Hyuck; Lee, Jeong-Hee; Kim, Dong Chul; Yang, Jung Wook; Kim, Min Hye; Seo, Deok Ha; Jang, Se Min; Lee, Jong Sil
Aim: To examine the expression of RAB27A and RAB27B in clear cell renal cell carcinoma (CCRCC).Materials & methods: The intensity and proportion of tumor cells staining positive for RAB27A and RAB27B in a total of 304 cores were evaluated.Results: The T stage showed a significant correlation with RAB27A intensity (p < 0.001). In multivariate analysis, CCRCC with negative intensity of RAB27A expression demonstrated poor disease-specific survival (hazard ratio: 6.821, 95% CI: 1.128–41.241; p-value = 0.036).Conclusion: RAB27A is an independent prognostic factor in CCRCC.